#### Princezz3286

##### Junior Member

- Joined
- Nov 12, 2005

- Messages
- 66

(z + 2) (z + 2) = -z (3z + 4) + 9

(z + 2) (z + 2) = (-3z^2 - 4z + 9) * -1

(z + 2) (z + 2) = 3z^2 + 4z - 9

above is my work process, but this is where I am stuck because I can't factor 3z^2 + 4z - 9.... please let me know where to go from here.

70) 15t^3 + 40t = 70t^2

-70t^2 = -70t^2

------------------------------------

15t^3 - 70t^2 + 40t = 0

5t(3t^2 - 14t + 8) = 0

5t[(3t - 2)(t - 4)]= 0

where do I go from here? I don't get it?

HELP

Thank You!

Heather